Clinical Effect of Photobiomodulation on Wound Healing of Diabetic Foot Ulcers: Does Skin Color Needs to Be Considered? - Thabo Dhlamini; Nicolette Nadene Houreld (Journal of Diabetes Research)
Diabetic foot ulcers (DFUs) are one of the most common complications of diabetes. DFUs impede patients’ quality of life and are known to be unresponsive to conventional therapy. Photobiomodulation (PBM) is a pain-free, noninvasive treatment method that has been shown to promote chronic wound healing and has been successfully used for the treatment of DFUs. Since skin tone and color can affect the way light interacts with tissue, studies should take this into consideration when determining protocols for the use of PBM. This review is aimed at critically evaluating data of existing studies conducted to evaluate the clinical effect of PBM on DFUs, taking skin color into consideration. A literature search was conducted and resulted in articles on cell studies, animal studies, and clinical trials. Only 13 clinical trials and 2 clinical case studies were adopted and used in this review. All the clinical trials adopted for this review show evidence that PBM together with conventional treatment results in an increased healing rate of DFUs; however, only one study adjusted their protocol according to skin color. There are not enough studies conducted on people of color to determine the safety and efficacy of PBM therapy in such ethnic groups. Future randomized, placebo-controlled clinical trials are necessary on PBM and DFUs and should take skin color into consideration.